Millennial Lifestyle Mediated: Financial Literacy and Income on Investment Decision - Ida Rosnidah; Kartono Kartono; Inne Isnaeni Nurul Jannah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research seeks to assess the impact of financial literacy and income on lifestyle, examining their implications on investment decision-making behavior within the millennial generation (based on a survey of residents in Cirebon city). The research is conducted in the city of Cirebon. This research adopts a quantitative approach employing a survey method administered to residents of Cirebon City falling within the millennial generation category, i.e., individuals born between 1981 and 1996. The focal points of this study encompass financial literacy, income, lifestyle, and investment decisions. The sample size for this research is set at 100 respondents, determined through the employment of judgment sampling. The analysis employed in this study is Structural Equation Modeling (SEM), facilitated by the Smart PLS 3 computer program. The findings of this research reveal that both financial literacy and income exert an influence on the respondents' lifestyle. Additionally, financial literacy, income, and lifestyle collectively impact the investment decisions made by the respondents.